The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3762/bjoc.5.18
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative cyclization of alkenols with Oxone using a miniflow reactor

Abstract: SummaryA miniflow system for oxidative cyclization of alkenols with Oxone was developed. Thus, the oxidative cyclization of (Z)- and (E)-alkenols in i-PrOH with an aqueous solution of Oxone proceeded smoothly and safely in a PTFE tube without any exogenous catalytic species, and was subsequently quenched in a flow-reaction manner to afford the corresponding furanyl and pyranyl carbinols quantitatively within 5 or 10 min of residence time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Uozumi et al demonstrated that these potentially hazardous conditions could be overcome by the use of a microfluidic system. 330 The microreactor was composed of PTFE tubing (1mm ID, 40 µL) and was used for the oxidative cyclization of alkenols. With a residence time of 5 minutes and temperature set at 80 °C, the reaction proceeded smoothly to afford the corresponding cyclic ethers in high conversion (70-99%).…”
Section: Electrochemical Oxidation Processes In Continuous Flowmentioning
confidence: 99%
“…Uozumi et al demonstrated that these potentially hazardous conditions could be overcome by the use of a microfluidic system. 330 The microreactor was composed of PTFE tubing (1mm ID, 40 µL) and was used for the oxidative cyclization of alkenols. With a residence time of 5 minutes and temperature set at 80 °C, the reaction proceeded smoothly to afford the corresponding cyclic ethers in high conversion (70-99%).…”
Section: Electrochemical Oxidation Processes In Continuous Flowmentioning
confidence: 99%
“…[α] 20 D = -8.21 (c 1.43 2,118.9,63.9,61.2,58.4,36.2,27.1,24.8,21.0,18.7,16.4. MS: 212 (M + ),207,197,170,152,137,126,119,109,94,81,71,59,43.…”
Section: Synthesis Of 6-acetoxymentioning
confidence: 99%
“…[1,2] Several 2,2,6-trisubstituted-tetrahydropyran-3-ols exhibit excellent perfumery properties . The oxidation of monoterpenes has important industrial applications because their epoxides are used for their olfactory properties and as starting materials for the synthesis of commercially important fragrances and flavouring materials.…”
Section: Introductionmentioning
confidence: 99%
“…An oxidative cyclization of alkenols could be effectively and safely performed in a flow manner using oxone (2KHSO 5 .KHSO 4 .K 2 SO 4 ) as an oxidizing agent without the need for any catalytic species [25]. Using aqueous conditions, a selection of cyclic ethers were prepared in a very short reaction time (5-10 min), under mild conditions (80 C) and in satisfactory conversions (70-99%).…”
Section: Five-membered Ring Heterocycles With One Heteroatommentioning
confidence: 99%
“…Oxone (2KHSO 5 .KHSO 4 .K 2 SO 4 ) was used by Uozumi and coworkers as an oxidizing agent for the oxidative cyclization of alkenols [25]. Using aqueous conditions, threo-tetrahydropyranyl alcohol was prepared in 90% conversion from the starting acyclic alcohol.…”
Section: Six-membered Ring Heterocycles With One Heteroatommentioning
confidence: 99%